JAMINAN SOSIAL MELALUI VOUCHER NASIONAL WAKAF - ANDRIANI SYOFYAN (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2018)
This paper aims to see how big the potential of cash waqf through national voucher waqf in Indonesia and how big the potential of national vouchers on social security consisting of health, education and venture capital. This paper uses the writing of quantitative methods. Where this paper describes the collection of cash waqf through a national voucher consisting of a national voucher Rp. 5.000,-, national voucher Rp. 10.000,- national voucher Rp. 20.000,-, national voucher Rp. 50.000,-, and national voucher Rp. 100.000,- which is burdened to the Indonesian society aged 15 years and over, along with the potential and empowerment of cash waqf obtained from the national voucher that will be allocated to health, education and venture capital.